Stable Equatorial Ice Belts at High Obliquity in a Coupled Atmosphere–Ocean Model - Kilic, Cevahir; Lunkeit, Frank; Raible, Christoph C.; Stocker, Thomas F. (The Astrophysical Journal, 2018)
Various climate states at high obliquity are realized for a range of stellar irradiance using a dynamical atmosphere–ocean–sea ice climate model in an Aquaplanet configuration. Three stable climate states are obtained that differ in the extent of the sea ice cover. For low values of irradiance the model simulates a Cryoplanet that has a perennial global sea ice cover. By increasing stellar irradiance, transitions occur to an Uncapped Cryoplanet with a perennial equatorial sea ice belt, and eventually to an Aquaplanet with no ice. Using an emulator model we find that the Uncapped Cryoplanet is a robust stable state for a range of irradiance and high obliquities and contrast earlier results that high-obliquity climate states with an equatorial ice belt may be unsustainable or unachievable. When the meridional ocean heat flux is strengthened, the parameter range permitting a stable Uncapped Cryoplanet decreases due to melting of equatorial sea ice. Beyond a critical threshold of meridional ocean heat flux, the perennial equatorial ice belt disappears. Therefore, a vigorous ocean circulation may render it unstable. Our results suggest that perennial equatorial ice cover is a viable climate state of a high-obliquity exoplanet. However, due to multiple equilibria, this state is only reached from more glaciated conditions, and not from less glaciated conditions.